Customers' perception of residential photovoltaic solar projects in the UAE: A structural equation modeling approach - Haneen Abuzaid (Elsevier, 2022)
Photovoltaic solar systems are widely used as a renewable energy resource worldwide due to the numerous negative impacts of the conventional-depleted energy resources. In the context of the Middle East, the United Arab Emirates has been a pioneer in regulating renewable energy and setting annual targets for the dependency on and market share of renewable energy and carbon dioxide emissions. The purpose of this paper is to define the main factors that affect customers' perception of photovoltaic solar projects for the residential sector as an alternative renewable source of electricity in the United Arab Emirates. Reliably collected responses were used to build a hypothetical model using confirmatory factor analysis and structural equation modeling. The findings showed that financial and environmental aspects are the main contributors to customers' perception in the United Arab Emirates. Furthermore, it was apparent that different nationalities in the United Arab Emirates have similar average perception of photovoltaic systems projects and finally, we suggest that perception may positively impact the intention towards adopting residential photovoltaic systems. These findings can be utilized by governmental related authorities, photovoltaic systems contractors, photovoltaic systems leasing companies, and energy consultants to enhance the perception of customers and increase the tendency to install such projects in the residential sector.